Differences in lower limb biomechanics between ballet dancers and non-dancers during functional landing tasks. (July 2018) - Harwood, Annissa; Campbell, Amity; Hendry, Danica; Ng, Leo; Wild, Catherine Y.
Abstract: Objectives: To determine the differences in the lower limb landing biomechanics of adolescent ballet dancers compared to non-dancers when performing a hop and a stop jump task. Design: Cross-sectional. Setting: Laboratory. Participants: Thirteen adolescent female ballet dancers (11.8 ± 1.1 years) and 17 non-dancers (10.9 ± 0.8 years) performed hop and stop jump tasks. Main outcome measures: Vertical ground reaction force, and three-dimensional ankle, knee and hip joint angles and moments during the landing phase. Results: Dancers displayed greater sagittal plane joint excursions during the hop and stop jump at the ankle (mean difference = 22.0°, P  < 0.001, 14.8°, P  < 0.001 respectively), knee (mean difference = 18.1°, P  = 0.001, 9.8°, P  = 0.002 respectively) and hip (stop jump task; mean difference = 8.3°, P  = 0.008). Dancers displayed a larger hip extensor moment compared to non-dancers ( P  < 0.001) during the stop jump task only. Dancers also took longer to reach peak vGRF and jumped three times higher than non-dancers ( P  < 0.001) during the stop jump task. No difference in peak vGRF between groups was displayed for either task. Conclusions: Adolescent dancers demonstrate a transfer of landing technique to non-ballet specific tasks, reflective of the greater jump height and sagittal plane joint excursions. This landing strategy may be associated with the low rate of non-contact ACL injuries in female dancers. Highlights: Dancers jump higher but land with similar vGRF compared to non-dancers. Dancers display greater sagittal plane lower limb joint excursions. Dancers transfer their landing technique to non-ballet-specific tasks.